Tingkat Stres Berdasarkan Jenis Stresor Pada Mahasiswa Tingkat Akhir Tahap Akademik Fakultas Kedokteran Unisba - Afif Januar Ginata; Ratna Dewi Indi Astuti; Julia Hartati (Bandung Conference Series: Medical Science, 2023)
Abstract. Stress is a common phenomenon and cannot be avoided by everyone. Stress is an unpleasant condition and can elicit a response be it mental, physical, emotional, and spiritual of a person. The occurrence of stress is caused by a stimulus called a stressor. A person who experiences stress brings up signs according to their stress level, be it mild, moderate, or severe levels. The aims of study to determine the picture of stress levels based on the type of stressor assessed using the Medical Student Stressor Questionnaire in final year students of the academic stage of the Faculty of Medicine Unisba. This research is a descriptive study with a cross sectional approach with the number of samples is 130 students. The results of this study found that the level of stress in general most occurs in moderate stress reaching 46.92%, the level of stress based on Academic Related Stressor most occurs in severe stress reaching 40.77%, stress levels based on Interpersonal and Intrapersonal Related Stressors, Teaching and Learning Related Stressors, Social Related Stressors, and Group Activities Related Stressor is dominated by moderate stress, the level of stress based on Drive & Desire Related Stressor occurs the most in mild stress reaching 37.69%. The occurrence of differences in stress levels in each individual is due to several influencing factors such as the ability of individuals to perceive stressors, the time of exposure to stressors, and the number of stressors that must be faced in the same period of time. Abstrak. Stres merupakan fenomena umum dan tidak dapat dihindari oleh setiap orang. Stres adalah kondisi yang tidak menyenangkan dan dapat menimbulkan respon baik itu mental, fisik, emosional, dan spiritual seseorang. Terjadinya stres disebabkan oleh suatu stimulus yang disebut sebagai stresor. Seseorang yang mengalami stres memunculkan tanda-tanda sesuai dengan tingkat stresnya, baik itu tingkat ringan, sedang, maupun berat. Penelitian ini bertujuan untuk mengetahui gambaran tingkat stres berdasarkan jenis stresor yang dinilai menggunakan Medical Student Stressor Questionnaire pada mahasiswa tingkat akhir tahap akademik Fakultas Kedokteran Unisba. Penelitian ini merupakan penelitian deskriptif dengan pendekatan cross sectional dengan jumlah sampel sebanyak 130 mahasiswa. Hasil penelitian ini didapatkan bahwa tingkat stres secara umum paling banyak terjadi pada stres sedang mencapai 46,92%, tingkat stres berdasarkan Academic Related Stressor paling banyak terjadi pada stres berat mencapai 40,77%, tingkat stres berdasarkan Interpersonal and Intrapersonal Related Stressor, Teaching and Learning Related Stressor, Social Related Stressor, dan Group Activities Related Stressor didominasi dengan stres sedang, tingkat stres berdasarkan Drive & Desire Related Stressor paling banyak terjadi pada stres ringan mencapai 37,69%. Terjadinya perbedaan tingkatan stres pada masing-masing individu disebabkan karena adanya beberapa faktor yang mempengaruhi seperti kemampuan individu dalam mempersepsikan stresor, waktu paparan stresor, dan banyaknya stresor yang harus di hadapi dalam jangka waktu yang bersamaan.